TANGGUNGJAWAB PRIVATE KARYAWAN DAN PERUSAHAAN TERHADAP KERUGIAN KONSUMEN - Mukhtar; Septyanun, Nurjannah; Erwin, Yulias (LPPM STIH Awang Long, 2023)
In this trading activity, it is hoped that there will be a balance between the rights and obligations of business actors and consumers. For this reason, studying the implementation of private responsibilities of business actors in fulfilling consumer rights in terms of positive law in Indonesia is an interesting thing to study. The objectives of this research are 1) to find out and analyze the private responsibility of employees and companies for consumer losses in terms of positive law in Indonesia; and 2) to find out the judge's legal reasoning regarding consumer dispute decisions in the PN.Sel decision Number 9/Pdt.G.S/2020/PN.Sel. This study uses doctrinal normative legal research, namely a process for finding legal rules, legal principles, and legal doctrines to answer the legal issues faced. The approach used to obtain data for analysis is first, the statutory approach, second, the legal case study approach, third, the conceptual approach. This study uses qualitative data analysis, where the data is analyzed using descriptive analysis methods. From the results of the discussion, it was concluded that 1) The private responsibility of employees and companies for consumer losses in terms of positive law in Indonesia should be rejected from the start because Defendant I is a subject domiciled in Jakarta who should be a co-Defendant, and Defendant II became Defendant I, where Defendant one had no legal relationship because Defendant I was only the employer of Defendant II. The defendant cannot make an exception in accordance with the provisions of Article 20 of Supreme Court Regulation Number 4 of 2019 concerning Amendments to Supreme Court Regulation Number 2 of 2015 concerning Methods for Settlement of Simple Claims; and 2) The decision in case Number 9/Pdt.G.S/2020/PN.Sel should be rejected, because Defendants one and two are unclear in accordance with the Plaintiff's claim and there is a discrepancy regarding the position of Defendants I and Defendants II, so that the Panel of Judges handling this case must be based on the concept of Legal reasoning.